Singing in Greek : a guide to Greek lyric diction and vocal repertoire - Zervanos, Lydía, 1984- (Guides to lyric diction., 2015)
In Singing in Greek: A Guide to Greek Lyric Diction and Vocal Repertoire Lydía Zervanos reveals to singers the vast riches of Greek vocal music.